STUDI EKSPLORASI PEREMPUAN DESA MOTAULUN YANG HAMIL DI LUAR NIKAH KECAMATAN MALAKA BARAT KABUPATEN MALAKA - Leki, Susdi Ice Yani; Klau, Erni Raster; Mardani, Ambara Saraswati (Education For All, 2024)
This research is motivated by the phenomenon of women getting pregnant out of wedlock. This occurs due to the rise of promiscuity and also because of the weakness of faith in a person which ultimately affects the lives of individuals, so this research aims to find out the factors that cause women in Motaulun Village to become pregnant out of wedlock. The method used is a qualitative method with an exploratory case study approach used to explore the phenomenon of a perpetrator informant who is pregnant out of wedlock. The technique used to collect data is interviews, observation and documentation studies. Mataulun who were pregnant out of wedlock at the age of 13-19 years were pregnant out of wedlock. The research results were grouped based on themes, namely the factors causing women to become pregnant outside of marriage and the impact of women becoming pregnant outside of marriage. The first. Factors that cause women to become pregnant out of wedlock include: parenting style factors in the form of a lack of control or supervision from parents and people often giving children freedom, the existence of social media in the form of Facebook and WhatsApp so that informants and partners crave each other's messages through these media and social comparisons. namely, the perpetrator informant always follows other people's styles and always compares himself with other people. The second impact of women being pregnant out of wedlock includes: psychological impacts in the form of teenage girls feeling uncomfortable, afraid, anxious and depressed.